Tipologi Kejahatan Pelaku Begal Kendaraan Bermotor - Lutifyani, Mawarda; Aura, Raissa Rahma; Novitrisani, Yulinda; Supriyadi, Tugimin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
One form of criminal behavior that often occurs today is robbery crime. Robbery problems usually occur at night, taking advantage of the lack of lighting and infrastructure, and the victims are often threatened, injured or killed. This research uses a literature review or literature study method by collecting data in the form of journal articles obtained through websites, especially Google Scholar. From the results of the article search, it was found that the robbers carried out the robbery due to internal and external factors.